2020
DOI: 10.1007/s11187-020-00405-0
|View full text |Cite
|
Sign up to set email alerts
|

Male and female entrepreneurs’ employment growth ambitions: the contingent role of regulatory efficiency

Abstract: Entrepreneurs start and grow their ventures in a widely varying set of institutional contexts. One differentiator is a country’s regulatory efficiency which encompasses the freedom to start and to run a business without excessive government interventions around registering, hiring, and firing employees, and price controls on currency. The efficiency of regulations varies substantially among countries and imposes additional costs and risks on entrepreneurs’ activities. We integrate insights from institutional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…In the case of Vietnam, we show a tendency of women to lead medium-size firms with better performance in the formal sector. Some cross-country studies show male entrepreneurs have significantly greater venture employment growth ambitions than their female peers (Darnihamedani and Terjesen 2020) and male-owned firms are often in large size than those owned by women. Amin ( 2011) looks specifically at the informal sector of unregistered firms in Argentina and Peru and confirmed the female-owned firms under-performance hypothesis within various sub-samples of firms with different magnitudes of difference.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In the case of Vietnam, we show a tendency of women to lead medium-size firms with better performance in the formal sector. Some cross-country studies show male entrepreneurs have significantly greater venture employment growth ambitions than their female peers (Darnihamedani and Terjesen 2020) and male-owned firms are often in large size than those owned by women. Amin ( 2011) looks specifically at the informal sector of unregistered firms in Argentina and Peru and confirmed the female-owned firms under-performance hypothesis within various sub-samples of firms with different magnitudes of difference.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…To explore the relationship between economic freedom and the establishment of formal business, we have generated panel data based on the intersection of available information from (1) the Fraser Institute Freedom Index (Díaz-Casero et al, 2012;Gwartney et al, 2021;Nyström, 2008), (2) The World Bank entrepreneurship survey (Ajide, 2021;Goel & Saunoris, 2020), and (3) The World Bank indicators (Angulo-Guerrero et al, 2017;Darnihamedani & Terjesen, 2020;Fuentelsaz et al, 2015b;Kosi & Bojnec, 2013;McMullen et al, 2008;Nyström, 2008;Özkul, 2020). The final sample included information of 107 countries over six years, 2013 to 2018.…”
Section: Datamentioning
confidence: 99%
“…The hiring expectations of solo entrepreneurs have been studied by Van Stel et al (2020), who concluded that solo entrepreneurs with high educational levels tend to have low hiring intentions and that these low intentions are due to the need for autonomy and self-expression or self-realization. Darnihamedani and Terjesen (2020) analyzed the hiring expectations of entrepreneurs from the perspective of regulatory efficiency, composed of business freedom, labor freedom, and monetary freedom. After analyzing 68 countries, they concluded that entrepreneurs in countries with fewer labor restrictions and greater monetary freedom have higher growth ambitions.…”
Section: Job Creation Expectationmentioning
confidence: 99%